The functional impact of remote ischaemic preconditioning on patients undergoing first time coronary artery bypass surgery. (22nd September 2015) - Rahman, IA; Nightingale, P; Marsh, AM; Williams, L; Mascaro, CJ; Bonser, RS; Steeds, R
Abstract : Objectives: Previous studies have documented a reduction in perioperative myocardial troponin release with remote ischaemic preconditioning (RIPC) during on-pump coronary artery bypass grafting (CABG) surgery. Whether this confers a practical benefit is not known. A manifestation of myocardial protection is the conservation of ventricular function. The aim of this study was to determine whether RIPC would result in a relative improvement in left ventricular and right ventricular function on echocardiography. Methods: In a double-blind, randomised controlled study, the effect of three cycles of left upper limb tourniquet inflation (200 mm Hg for 5 minutess) and deflation (5 minutess) prebypass was compared in non-diabetic adults undergoing on-pump CABG utilising cold blood cardioplegia. Transthoracic echocardiography with left ventricular contrast opacification was performed 1–3 days before and 5–7 days following surgery. The ischaemic stimulus was confirmed by the loss of digital pulse oximetry during cuff inflation. Results: 49 patients were recruited (RIPC 24; control 25). Patients received median four (interquartile range 3–4) grafts with no difference in age (65.4 ± 7.3 years), sex (88% male), Euroscore (3.5 ± 2.2%), cross-clamp time (74.8 ± 20.1 minutess) or bypass time (96.5 ± 24.5 minutess). Changes in functional parameters in the whole cohort are shown in the table. Of all parameters, only tricuspid annular plane systolic excursion (TAPSE) declined during CABG (p<0.001). Between groups, there was no difference in remote versus controls (ΔLVEDvol.index −3.9 ± 16.9 vs −4.1 ± 15.2; ΔLVESvol.index −2.3 ± 10.4 vs 0.01 ± 9.3; ΔLVEF −0.2 ± 15.7 vs −0.2 ± 17.0; left ventricular diastolic relaxation (ΔLV Tei −0.7 ± 0.3 vs −0.6 ± 0.2; ΔE/Em 3.2 ± 15.7 vs 1.8 ± 7.6); isovolumic acceleration (0.2 ± 0.8 vs 0.1 ± 1.0)). For right ventricular function there was no difference in right ventricular internal diameter (ΔRVIDd) 0.06 ± 0.58 vs −0.08 ± 0.7 or right ventricular relaxation (ΔRV Tei) −0.02 ± 0.25 vs −0.07 ± 0.3 but ΔTAPSE was significantly worse in the remote patients 12.8 ± 4.6 versus 8.4 ± 4.8 mm (p = 0.011). Conclusion: RIPC before on-pump CABG does not protect left ventricular function on echocardiography. RIPC is associated with an additional reduction in right ventricular longitudinal function and does not protect right ventricular global function.